Design of a Human Body Temperature Measuring Instrument with a Contactless Based System Internet of Things - Santoso, Gatot; Firman, Beny; Hani, Slamet; Raharjo, Suwanto; Setyaningsih, Emy; Prasetyo, Ragil (Engineering And Technology Journal, 2023)
Measuring body temperature is one way of physical assessment that is used to determine the state of human health or to test human responses. This factor is the most important to detect whether a person is experiencing symptoms of disease or not.A human body temperature measuring system with a contactless system will help health agencies in determining a visitor or patient in knowing whether they are healthy or sick. The results of this research show that the body temperature measuring device with a contactless system using the mlx90614 temperature sensor can work well in accordance with the design with a large accuracy of 98.44% with the ratio of conventional body temperature measuring devices.